2019
DOI: 10.14723/tmrsj.44.109
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for estimating ultimate clamp force in lag screw timber joints with steel side plates

Abstract: This paper proposes a numerical method for estimating the ultimate clamp force of lag screw timber joints with steel side plates based on the pull-out strength and thread friction coefficient of the lag screw. Lag screw tightening tests and pull-out tests were performed using timber samples from three different wood species, for three different screw insertion angles with respect to the annual ring, to evaluate how well the predictions matched the observed empirical data. Ratios of observed to estimated ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, to implement these joining methods in actual buildings, it is important to maintain the axial force for a long period of time, and, in addition, axial force management during construction is also an important issue. Thus far, the authors have revealed, with regard to axial force management, that the so-called torque method, which manages wood joints using a single bolt or a single lag screw with a tool, such as a torque wrench, can be applied and that axial force generated while tightening a lag screw is lower than the pull-out strength of the lag screw, owing to the effects of friction at the threaded part [10][11][12][13][14]. However, for joint types formed with multiple bolts, such as the wood friction connectors proposed by the authors, sequential tightening of each bolt affects deformation around each of the other bolts.…”
Section: Introductionmentioning
confidence: 99%
“…However, to implement these joining methods in actual buildings, it is important to maintain the axial force for a long period of time, and, in addition, axial force management during construction is also an important issue. Thus far, the authors have revealed, with regard to axial force management, that the so-called torque method, which manages wood joints using a single bolt or a single lag screw with a tool, such as a torque wrench, can be applied and that axial force generated while tightening a lag screw is lower than the pull-out strength of the lag screw, owing to the effects of friction at the threaded part [10][11][12][13][14]. However, for joint types formed with multiple bolts, such as the wood friction connectors proposed by the authors, sequential tightening of each bolt affects deformation around each of the other bolts.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have long been interested in developing load-bearing walls, which leverage the friction created when wooden members are fastened together (or to steel plate) with bolts or lag screws. Our team has already reported on the structural performance of these joints [9][10][11], how to control the initial tightening force [12][13][14][15], and their long-term stress relaxation behavior [16][17][18]. In the last case, we have shown that these joints can withstand relatively high stress when the initial tightening force exceeds the compressive yield point of the wood, even when exposed to repeated wetdry cycles [18]; and that they can withstand at least 70% of any vertical compressive stress applied to the wood, even in a high-temperature, constant-humidity environment [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the driving, tightening and stripping torques were established in direct relation to different specimen thicknesses of t = 12, 16, and 20 mm. Matsubara et al, 20 Eckardt, 21 Steilner 11 for instance, investigated forces that appear in screwed engineered wood products. Kuang et al 22 and Tor et al 23,24 investigated the appearing screw torques in relation to applicable pilot holes and screw penetration depths in engineered wood products.…”
Section: Introductionmentioning
confidence: 99%